The weaponization of artificial intelligence (AI) and its implications on the security dilemma between states: could it create a situation similar to "mutually assured destruction" (MAD) - Dahab, Gilan Osama (AUC Knowledge Fountain, 2019)
There is no a consensus in the IR literature on the possible implications of AI for cyber or nuclear capabilities, and whether AI would exacerbate, or potentially mitigate, the security dilemma between actors with varying capabilities. This capstone project explores these questions, using experts' interviews and secondary data. It has tackled the issue under study by using the most-similar method in which most of the variables are similar. The paper argues the weaponization of AI exacerbates the security dilemma between states since it increases uncertainty. What is actually problematic about the military AI applications, as opposed to other military capabilities, is the declining role of humans. AI could be productive and counterproductive when it comes to policy making, implying the necessity of keeping humans over-the-loop. Neutralization makes AI deterrence reasonable for avoiding destructive, disruptive and manipulative outcomes. Like nuclear capabilities, establishing an AI-MAD structure, regulating the uses of AI and establishing a governing regime for AI arms race are the best possible policies. Keywords: Artificial Intelligence, Deterrence, Mutually Assured Destruction, Arms Control